Characteristics of Moslem Families Economy Based on Maqashid Sharia Perspective - Zakiy, Faris Shalahuddin; Ridwan, Ahmad Muhtadi; Supriyanto, Achmad Sani (Journal of Islamic Economic Laws, 2021)
Modern lifestyle has interfered principles of moslem families. This era tries to define attitude, wealth value, and social position of individuals in society. It might become a doctrine, patent product, challenge or threat. The objective of this research is to elaborate the Islamic characteristics within the economy of moslem families and also implementation of Maqashid Sharia in the economy of moslem families. This research exerts case-study, by determining selected informants from the community of moslem small entrepreneurs in Malang. The findings show that the moslem families consider faith (iman) as basic foundation of economy. They also hold on to character perfection that is based on akhlaqul karimah, lawfulness and wholesomeness, priority scale as expenditure reference, moderation as absolute standardization and responsibility of woman’s wealth proprietary. Internalization of Islamic economy principles in the moslem families economy includes the statement that working as a form of ikhtiar and worship, expenditure as material and spiritual distribution of wealth, savings as urgent post in the future, and wealth as instrument to serve to Allah. Finally, it is important to regard Maqashid Sharia as a standard of Muslim action in economy.